Minicholecystectomy, Experience of 100 Cases At Continental Medical College, Township, Lahore - IMRAN SAEED, SUHAIL ANJUM (Journal of Fatima Jinnah Medical University, 2018)
Background: The standard treatment of gallstone disease has been cholecystectomy through a sub costal 7-10 cm incision. New techniques & procedures are developing in surgery aiming at decreasing tissue damage, pain, complications & stay in the hospital. This study was conducted to assess cholecystectomy through 5 cm sub costal incision. Materials & Methods: This descriptive study was conducted at Department of Surgery, Ch. Rehmat Ali Memorial Hospital, Township, Lahore from January 2008 to December 2010. Cholecystectomy was performed through 5 cm sub costal incision. Both sexes were included in the study irrespective of age & duration of illness. Both acute & chronic cholecystitis was included. The total number of patients was 100; ninety were females & ten males. Mean age was 45 years. Ninety patients had chronic cholecystitis, five had acute cholecystitis & five had mucocele of gall bladder. Suction drains were placed in 10 patients. Results: 100 patients with cholelithiasis were included in the study that underwent minicholecystectomy. In 10 cases the incision had to be enlarged because of difficulty in identifying anatomical landmarks. The average operating time was 50 minutes & average blood loss was 100 ml. The average post operative stay in hospital was 2 days.